Aproveitamento dos resíduos de açaí para obtenção de combustíveis sustentáveis - Marinho, Cybelle Crystinne do Prado (2023)
Alternatives to the use of açaí seed (Euterpe oleracea Mart) have been investigated to reduce the impacts caused by the excess production of these residues. It consists of peel, pulp and seed, the latter being the largest part of the fruit, about 80%. The civil aviation sector has focused on sustainable aviation fuels and has invested in using agro-industrial waste to produce sustainable fuel. Since aviation has a huge impact on the climate system, it is responsible for 2% to 3% of total greenhouse gas emissions from anthropogenic actions. In this context, the objective of this project is to evaluate the process of pyrolysis of açaí residual biomass to obtain sustainable aviation fuel. In this work, the study of açaí seed in natura (IN) and with pretreatment of sulfuric acid at a concentration of 3M (PT-3M) before the pyrolysis process was investigated. The biomasses were evaluated in terms of immediate analysis and proceeded to the pre-treatment stage including characterization through DSC, FTIR, TGA and PCS analyses. Posteriorly, the pyrolysis experiments were conducted under two temperatures (450 °C and 500 °C), heating rate (50 °C/min), with nitrogen flow rate (5 L/min) and time (5 min). The pyrolysis products were characterized by means of Thermogravimetric Analysis (TGA), Fourier Transform Infrared Spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC). The immediate analysis of the açaí seeds presented relevant results with those found in the literature, a high value of volatile materials in 78.06% and a reduced value of ash in 1.17%. The superior calorific power (PCS) carried out in the calorimetric bomb of the IN and PT-3M biomass of the açaí seed were 16.28 MJ/kg and 18.60 MJ/kg, respectively, presenting themselves as potential biomass for bioenergy production. The result for the bio-oil, a pyrolysis product, was satisfactory and attested in the analyzes carried out. Another product of the pyrolysis evaluated was the biochar, its results presented themselves as an alternative of solid fuel for the generation of heat and energy, presenting a PCS of approximately 31 MJ/kg.